ChemInform Abstract: Reductive Removal of Methoxyacetyl Protective Group Using Sodium Borohydride. Issue 25 (24th June 2014) - Gadekar, Pradip K.; Hoermann, Maryann; Corbo, Faith; Sharma, Rajiv; Sarveswari, S.; Roychowdhury, Abhijit
Abstract A selective reductive deprotection of methoxyacetyl‐protected alcohols and thiols is presented.